2005
DOI: 10.1007/s00418-005-0073-1
|View full text |Cite
|
Sign up to set email alerts
|

Nick-forming sequences may be involved in the organization of eukaryotic chromatin into ∼50 kbp loops

Abstract: Phenomena involving the disassembly of chromosomes to approximately 50 kbp double-stranded fragments upon protein denaturing treatments of normal and apoptotic mammalian nuclei as well as yeast protoplasts may be an indication of special, hypersensitive regions positioned regularly at loop-size intervals in the eukaryotic chromatin. Here we show evidence in yeast cell systems that loop-size fragmentation can occur in any phase of the cell cycle and that the plating efficiency of these cells is approximately 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
(47 reference statements)
0
16
0
Order By: Relevance
“…Consistent with this model of chromosome architecture, chromatin fragmentation phenomena have been observed that involve the preferential cleavage of DNA, presumably at the bases of loops (3). The global disassembly of chromatin to highmolecular-weight (Ն20-kbp) units also takes place upon alkali denaturation after proteinase digestion (4), at exposure to single-strand (ss)-specific nuclease (5), in the early stage of apoptotic DNA fragmentation (6), as well as in the case of healthy nonapoptotic mammalian and yeast cells upon various protein denaturing treatments (7,8). The DNase I hypersensitivity of mammalian chromatin at every Ϸ50 kbp (9), also detected in the vicinity of certain S/MARs (10), points to the special vulnerability of the DNA at the borders of supernucleosomal units of this size.…”
mentioning
confidence: 99%
“…Consistent with this model of chromosome architecture, chromatin fragmentation phenomena have been observed that involve the preferential cleavage of DNA, presumably at the bases of loops (3). The global disassembly of chromatin to highmolecular-weight (Ն20-kbp) units also takes place upon alkali denaturation after proteinase digestion (4), at exposure to single-strand (ss)-specific nuclease (5), in the early stage of apoptotic DNA fragmentation (6), as well as in the case of healthy nonapoptotic mammalian and yeast cells upon various protein denaturing treatments (7,8). The DNase I hypersensitivity of mammalian chromatin at every Ϸ50 kbp (9), also detected in the vicinity of certain S/MARs (10), points to the special vulnerability of the DNA at the borders of supernucleosomal units of this size.…”
mentioning
confidence: 99%
“…The Saccharomyces cerevisiae WDHY 199 (MATa, leu2-3,112 trp1-289 ura3-52 his7-2 lys1-1) cells were grown and the preparation of agarose-plugs containing the yeast spheroplasts was carried out as previously described (16). For restriction enzyme digestion, the plugs were preincubated in the appropriate 1× restriction enzyme buffers three times for 1 h each, then incubated with 150 U/ml SmaI or Nb.Bpu10I (Fermentas Life Science, Maryland, USA) in 200 μl of the same buffer at 37°C, for 1.5 h. For S1 nuclease treatment, 1× S1 buffer was used for washing of the plugs before digestion by 500 U/ml of the enzyme (Promega Life Science, Madison, USA) at 37°C, for 1.5 h. The plugs were finally equilibrated with TE buffer before electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…PCR was performed using 1.25 U of the Long PCR Enzyme mix (Fermentas) in 50 μl of 1× buffer supplemented with 1.5 mM MgCl 2 , containing, 20 pmol of each primer (Integrated DNA Technologies, Coralville, IA, USA), the dNTPs (Promega) at 0.25 mM concentration and 300 ng S. cerevisae genomic DNA prepared as described earlier (16). Each forward primer (see Tables 1–2 of Supplementary data) was used in pair with the reverse p1R primer resulting in variable length of amplicons, overlapping at their 3′-ends defined by the common reverse primer.…”
Section: Methodsmentioning
confidence: 99%
“…The existence of special, hypersensitive regions positioned regularly at approximately 50 kbp loop-size intervals in the eukaryotic chromatin was investigated by Szekvolgyi et al (2006). In yeast cell systems, they found that loop-size fragmentation can occur in any phase of the cell cycle.…”
Section: The Nucleus and Its Dynamic Compartmentsmentioning
confidence: 99%